Pengaruh Otago Home Exercise Programme terhadap penurunan tingkat risiko jatuh pada lansia di Desa Tegalrejo Kec. Merakurak - Dyah Pitaloka; Linda Yuni Alfiyanti; Nurus Safa’ah (Universitas Jenderal Achmad Yani Yogyakarta, 2023)
Background: The phenomenon of the risk of falling that occurs in the elderly in recent years has increased. Many cases of falls in the elderly result in soft tissue injuries, thigh and wrist fractures, and even death. Falling is a physical problem that is often experienced by the elderly, as you get older, the higher the decline in physical, mental and bodily functions.Objective: To Analyze the effect of the otago home exercise programme on decreasing the level of falling risk in the elderly in Tegalrejo Village, Merakurak District.Methods:The research used pra-experimental: pra-pasca test (one group pra-post design) with a cohort approach. The Sampling technique used was purposive sampling with a total sample of 102 elderly.Results: The results of the research conducted after being analyzed using the wilcoxon test with a significance level of α=<0.05, with value p = 0,000<0,05 value results Asymp sig(2-tailed)=0,000 which shows the influence between the two variables into a strong category with a positive direction.Conclusion: Otago home exercise programme has an effect on decreasing the level of falling risk in the elderly in Tegalrejo Village, Merakurak District.